Topaz : A Novel - Uris, Leon (New York Bantam Book, 1967)
A novel of international diplomacy and intrigue set in various locales around the world. Taking off from the Cuban missile crisis, the story is a combination of Russian espionage, the dedication of a French intelligence officer, and the devotion of the women in his life. Apparently the main point in the whole thing is the revelation of the direct line a Communist agency has to the top level in France. This is the secret of "Topaz."
Keywords: Cuba -- Novel